The Importance of Counseling Interventions for Early Childhood in Improving Emotional and Social Well-Being: A Literature Review - Muhammadi; Harnon; Johannes (PT Inovasi Pratama Internasional, 2024)
This study looks at how important counseling is for improving the emotional and social health of young children. We evaluated previous research in this area through a review of the literature, highlighting the benefits of counseling in the child's early developmental stages. This study found that timely and targeted counseling interventions in early childhood can improve emotional well-being, social development, and academic achievement. The focus of such interventions is often a counseling approach that is play-based, involves the family, and supports the child's independence. Counseling has also been shown to help young children avoid more serious behavioral or emotional problems in the future. The practical implications of these findings highlight the importance of a holistic approach to supporting early childhood development and highlight the need for investment in mentoring resources at the early childhood education level.